Revitalisasi Taman Baca Berbasis Partisipasi Masyarakat untuk Meningkatkan Minat Baca Anak Kelurahan Pipitan Kota Serang - Herlina Siregar; Fitri Pertiwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The declining function of the Pipitan Reading Park as a community literacy center is reflected in low children's attendance, the absence of structured literacy programs, and limited volunteer capacity in managing activities. This community service program aims to revitalize the reading park through the development of a child-friendly reading space, the implementation of creative literacy activities, and the establishment of a community-based volunteer team. The program employed a participatory approach consisting of preparation, implementation, evaluation, and follow-up stages, involving approximately 60 participants from various age groups. Program evaluation was conducted using pre-test and post-test assessments, participatory observation, participant satisfaction questionnaires, and focus group discussions. The results show an improvement in the average score from 2.8–3.0 to 4.42, representing an increase of approximately 47% from the initial condition. Beyond the numbers, the program generated broader social impacts: increased children's reading interest, the formation of an active volunteer team, and the establishment of a regular literacy activity schedule at the reading park. These findings indicate that a participatory approach grounded in local community needs is effective in revitalizing community reading parks and can serve as a practical model for sustainable community literacy development.